2016
DOI: 10.1080/10550887.2016.1189659
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in treatment and clinical characteristics among patients receiving extended release naltrexone

Abstract: Further research is needed to investigate real-world acceptability of extended-release naltrexone for alcohol and opioid use disorders, and potential gender differences. This study examines treatment and clinical characteristics among men and women receiving extended-release naltrexone in a large, publicly funded substance use disorder treatment system (N = 465; 52% female). Patient demographics, treatment characteristics, and the number of extended-release naltrexone doses received were collected from adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 28 publications
1
21
0
2
Order By: Relevance
“…Eight studies (44, 45, 48, 50, 55, 60, 61, 64) reported whether a variety of participant factors (e.g., demographics, drug use) were associated with XR-NTX adherence (Supplemental Table 2). Some variables were related to adherence but many of the associations were inconsistent across studies or reported only by one study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight studies (44, 45, 48, 50, 55, 60, 61, 64) reported whether a variety of participant factors (e.g., demographics, drug use) were associated with XR-NTX adherence (Supplemental Table 2). Some variables were related to adherence but many of the associations were inconsistent across studies or reported only by one study.…”
Section: Resultsmentioning
confidence: 99%
“…f Sample overlaps with that used in [54]. Only outcomes not reported in that study are reported for [57]. g Variable but included patient's residential stay (< 1 month) through follow-up, which occurred ≤ 10 days post-discharge.…”
Section: Prospective Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Naltrexone is an opioid antagonist that competitively blocks euphoric effects of heroin and other opioids, thereby preventing relapse of opioid abuse and overdose deaths when used as prescribed . It also reduces the craving for opioids and alcohol .…”
Section: Introductionmentioning
confidence: 99%
“…Potential gastrointestinal side effects of naltrexone may occur more often among women than men (Herbeck et al 2016) and include abdominal pain (11% vs. 8% in placebo), diarrhea (13% vs. 10% in placebo), nausea (29% vs. 11% in placebo), and vomiting (12% vs. 6% in placebo; Micromedex 2017c). Dizziness also appears to be more frequent with naltrexone (13% vs. 4% in placebo; Micromedex 2017c).…”
Section: Selection Of a Pharmacotherapymentioning
confidence: 99%